High-yield aqueous synthesis of partial-oxidized black phosphorus as layered nanodot photocatalysts for efficient visible-light driven degradation of emerging organic contaminants. (1st December 2022) - Liu, Jianqiao; Qu, Xiao; Zhang, Chuchen; Dong, Wenlong; Fu, Ce; Wang, Junsheng; Zhang, Qianru
Abstract: The layered nanodot derived from 2D materials is an emerging member of the advanced functional material family. However, its development in applications is still facing inevitable challenges, and one of them is the synthesis strategy with environmental consideration. Herein, we report an aqueous strategy for high-yield fabrication of black phosphorus (BP) layered nanodots. Without using any organic solvent, the initial red phosphorus (RP) fine powder is successfully converted to BP nanostructures at 180–205 °C under the low pressure of 2.7–7.8 MPa and the high yield of 78% is achieved. The synthesized BP nanodots are partial-oxidized, and demonstrate proficient photocatalytic abilities in the visible-light driven degradation of emerging organic contaminants. The photocatalytic mechanism of BP nanodots is dependent on the specific electronic band structure with an acceptor energy level at 0.6 eV above the valence band. The first principle calculation reveals that the surface oxidation layer assists the passivation by hydrogen in aqueous circumstance and establishes the receptor function of BP nanodots. Therefore, our study not only accomplishes a novel route for the environment-friendly fabrication of BP layered nanodot photocatalysts for efficient degradation of emerging organic contaminants, but also contributes to the in-depth understanding of layered nanodots. Graphical abstract: Image 1 Highlights: One-step green strategy for aqueous synthesis of BP layered nanodot photocatalysts. High yield of 78% from RP fine powder to BP at low pressure and temperature. Efficient visible-light photocatalytic degradation of emerging organic contaminants. Receptor function establishes a depletion layer of 0.3 nm under crystallite surface. Engineered band structure with acceptor energy level at 0.6 eV above valence band.